PERLINDUNGAN HUKUM BAGI NAZHIR DALAM PERSPEKTIF HUKUM PERWAKAFAN DI INDONESIA - Indri Eka Pratiwi; M. Sudirman; Sirajuddin Sailellah (Bajang Institute, 2025)
Wakaf is an Islamic legal institution that plays a strategic role in achieving the welfare of the community through sustainable asset management. As the wakaf manager, nazhir holds a crucial responsibility to ensure that wakaf assets are utilized in accordance with sharia objectives. However, nazhir often faces challenges in practice, such as limited legal knowledge, inadequate managerial capacity, and insufficient legal protection. These issues highlight the need for a thorough examination of legal protection for nazhir from the perspective of wakaf law in Indonesia, particularly based on Law Nomor 41 of 2004 on Wakaf.This study employs a Statute Approach, Conceptual Approach, Analytical Approach, and Case Approach. The research examines the implementation of legal norms in practice within society. Research data were obtained from primary sources, including laws and regulations, legal documents, and related literature, as well as secondary data collected through field studies. This study is grounded in the theory of justice, which emphasizes the importance of fair protection for nazhir, and legal theory, which views law as a tool to create social change.The findings reveal that legal protection for nazhir in Indonesia still faces obstacles, such as low legal literacy and weak oversight mechanisms. Legal protection for nazhir includes administrative protection, formal legal protection, protection from internal conflicts, and protection against abuse. Furthermore, institutions such as the Indonesian Wakaf Board (BWI) play a significant role in supporting the development, supervision, and empowerment of nazhir.